THE MANIFESTATION OF THE IMPLEMENTATION OF RSA ASYMMETRIC CRYPTOGRAPHY-BASED ELECTRONIC VOTING IN THE DIGITALIZATION OF SIMULTANEOUS REGIONAL HEAD ELECTIONS - Farhan Narendratama; Amalia Diamantina (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The conduct of simultaneous regional head elections in Indonesia to date remains predominantly dominated by conventional mechanisms that rely on the use of physical ballot papers and manual vote counting. In practice, such mechanisms give rise to various fundamental issues, including low effectiveness and efficiency in election administration, vulnerability to vote manipulation, inadequate protection of voter data, limited accessibility for vulnerable groups, and a high financial burden borne by regional government budgets. These conditions necessitate innovation in electoral governance that is adaptive to developments in information and communication technology. This article aims to analyze the urgency of implementing electronic voting in the administration of simultaneous regional head elections in Indonesia, as well as to formulate a conceptual design for the implementation of e-voting grounded in the principles of a democratic rule of law and good governance. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The findings indicate that the implementation of e-voting through a kiosk voting model supported by the Rivest–Shamir–Adleman (RSA) asymmetric cryptographic security system has the potential to enhance the accuracy of vote counting, ensure the confidentiality and integrity of voter data, expand access to political participation for vulnerable groups, and reduce election administration costs. With the strengthening of the regulatory framework and institutional readiness, e-voting may serve as a strategic instrument in promoting the digitalization of local democracy in Indonesia.